Applying keyword analysis to gendered language in the Íslendingasögur. Issue 2 (16th October 2014) - Blaxter, Tam T.; Andersen, Gisle; Hardt, Daniel
<x content-type="archive" xml:space="preserve">Abstract</x> Keyword analysis has been used to investigate properties of style and genre, as a tool in discourse analysis, and as a method of identifying differences between the speech of distinct social groups. It has often been criticised as a blunt tool which can exaggerate what differences are present and fails to distinguish between quite distinct phenomena. However, it remains a very powerful tool for wide analysis of systematic differences between corpora when used with sufficient scepticism. This paper uses keyword analysis to examine differences between the speech of male and female characters in the Íslendingasögur, narrative prose texts composed in Iceland in the 13th and 14th centuries. This dataset is of particular interest because such representations of speech are the only window on the language of social groups who were not involved in text production in medieval societies. It aims to demonstrate a rigorous application of keyword analysis, exemplifying what it can and, crucially, what it cannot show.